Applying ergonomics to dental scalers - Ahern, Stacey (Kansas State University, 2010)
The current state of the dental industry shows an increasing number of dentists and dental hygienists who are reducing hours and retiring early due to the injuries sustained while working. These injuries, or cumulative trauma disorders, can be reduced by applying ergonomics in dental tool design. The goal of ergonomics is to reduce current injuries but also prevent future ones. In addition, population demographics have shown an increasing trend in female dentists. With a shift from the male dominated field, design for different anthropometric measurements needs to be investigated. In order to pinpoint sources of pain, a survey was designed and distributed to dentists in Kansas, Missouri, and Texas. Even with a small sample size (n=24), results confirmed past studies in the dental industry of pain originating in the neck, shoulder, lower back, and wrist/hand region. The reasons stemmed from the repetitive motions and forces applied during dental procedures. Responses also found that ergonomic principles need to be applied to the handle and grip portion of dental scaler design. Dental scaling is the procedure to remove deposits on teeth, such as plaque and calculus, most commonly performed by dental hygienists. First, the history of dental tools, angulation, tool weight, and materials currently utilized were researched before looking into specific design factors for modification. Currently, the handle grip area on all dental tools range in size, but a 10 mm grip has been proven to be optimal. The optimal tool weight has yet to be determined as 15 grams is the lowest weight to be tested. Most tools are made of stainless steel and resins, which are not compressible. An experiment was designed to test a new dental scaler (A) made of a titanium rod with added compressibility in the precision grip area. The aim was to help reduce pressure on the fingers and hand muscles and increase comfort during scaling. The experiment utilized a Hu-Friedy sickle scaler (B) and a Practicon Montana Jack scaler (C) as controls to show two design spectrums, weight and material. The subjects (n=23) were taught the basics of scaling and required to scale using a typodont. The change in grip strength (Δ GS), pinch strength (Δ PS), and steadiness of the subjects hand were tested. An absolute and relative rating technique was utilized pinpointing that the new dental scaler was preferred with the eigenvector (A=0.8615, B=0.1279, C=0.0106). Statistical analysis confirmed this tool preference while also finding the interaction of gender and tool and Δ GS Tool A versus Tool B for males to be significant.
Keywords: Ergonomics; Tool design; Dental scalers; Engineering, Industrial (0546); Health Sciences, Dentistry (0567)